Factors Influencing Hotel and Restaurant Tax Revenues in the Regency/City of Yogyakarta Special Region 2011-2021 - Abdillah, Rais; Yuliawan, Dedy (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze the factors that influence Hotel and Restaurant Tax Revenue in the Special Region of Yogyakarta. This research uses 2 independent variables, namely: Number of tourist visits and Per Capita Income, and the dependent variable in this research is Hotel and Restaurant Tax Revenue. The data used is panel data. The scope of this research covers 5 regencies/cities in the Special Region of Yogyakarta Province using a 10-year time span, namely 2011 - 2021. The structural model that is estimated and has been tested significantly is REM. The results of this research show that the number of tourist visits has a positive and significant effect on hotel and restaurant tax revenues in the Yogyakarta Special Region, Per Capita Income has a positive and significant effect on Hotel and Restaurant Tax Revenues in the Yogyakarta Special Region.